An investigation of sensory processing skills in toddlers with joint hypermobility - Yildiz, Ayse; Yildiz, Ramazan; Burak, Mustafa; Zorlular, Rabia; Akkaya, Kamile Uzun; Elbasan, Bulent (Elsevier Ireland Ltd, 2024)
Background: Children with Generalized Joint Hypermobility (GJH) may have a motor developmental delay in the early period and subluxation, fatigue, autonomic dysfunction, and pain arising from ligaments and other soft tissues in advanced ages. Additionally, there is a loss of proprioceptive sensation in children and adults with GJH. Aims: This study aimed to evaluate sensory processing skills in toddlers with GJH. Study Design: A cross-sectional study. Subjects: Fifty-eight children aged between 12 and 14 months were included in the study. These children were divided into two groups: with and without GJH (31 with GJH and 27 without GJH). Outcome measures: The sensory processing skills of the children in the study were evaluated with the Test of Sensory Functions in Infants (TSFI). Results: The scores in the subtests of TSFI in response to tactile deep pressure, adaptive motor functions, visual- tactile integration, and response to vestibular stimuli were higher in favor of children without GJH (p p < 0.05). The total TSFI score was higher in the group without GJH (p < 0.05). Conclusions: Sensory processing problems were found in toddlers with GJH. Sensory motor development should be evaluated in children with GJH, and an appropriate early intervention program should be planned.
Keywords: Child; Proprioception; Sensory functions